Future Studies and the Development of Student Activities in Thai Higher Education Post-COVID-19 Pandemic - Abdullah Chelong (Journal of Organizational Innovation and Culture, 2022)
It is evident that the world today is changing rapidly and has an unexpected feature spreading vastly both physical and virtual. Likewise, the developments that occurred during the COVID-19 pandemic have undergone extraordinary changes expanding to every perimeter unprecedentedly. Previous knowledge and experiences are not always helpful in preparing for the future. It is necessary to create a perception and learning process for a new set of knowledge for the future, especially the perception of future studies. This article, therefore, has brought the issues of student activities development in higher education as an academic debate to significantly provide a body of knowledge to be used as a guideline for student development. It consists of 1) the importance of future studies and the development of student activities, 2) the trends of uncertainties affecting the future of student activities in higher education, and 3) the guidelines for applying the concept of future studies to student development.